2020
DOI: 10.1136/bmjopen-2020-038123
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother-to-child transmission of hepatitis B virus: protocol for a one-arm, open-label intervention study to estimate the optimal timing of tenofovir in pregnancy

Abstract: IntroductionHepatitis B virus (HBV) remains a public health threat and the main route of transmission is from mother to child (MTCT). Tenofovir disoproxil fumarate (TDF) treatment can reduce MTCT of HBV although the optimal timing to attain undetectable HBV DNA concentrations at delivery is unknown. This protocol describes the procedures following early initiation of maternal TDF prior to 20 weeks gestation to determine efficacy, safety and feasibility of this approach in a limited-resource setting.Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, though antiviral therapy is now well accepted for the women at high risk of MTCT, safety, timely initial drug administration, and discontinuation need to be elucidated. For example, Bierhoff et al [80] are conducting a study to evaluate the procedures following early initiation of maternal TDF, before 20 weeks of pregnancy, to determine the effectiveness, safety, and feasibility of this approach in a low-resource setting.…”
Section: Mother-to-child Transmission (Mtct)mentioning
confidence: 99%
“…However, though antiviral therapy is now well accepted for the women at high risk of MTCT, safety, timely initial drug administration, and discontinuation need to be elucidated. For example, Bierhoff et al [80] are conducting a study to evaluate the procedures following early initiation of maternal TDF, before 20 weeks of pregnancy, to determine the effectiveness, safety, and feasibility of this approach in a low-resource setting.…”
Section: Mother-to-child Transmission (Mtct)mentioning
confidence: 99%
“…Since its approval, additional studies have shown that anti-HBV NA administration during pregnancy can significantly reduce MTCT of HBV (Tavakolpour et al, 2018;Funk et al, 2021). Among them, tenofovir (TFV) is the only approved NA with high efficacy against the virus and no detected clinical resistance to date, and tenofovir disoproxil fumarate (TDF) treatment, a pro-drug of TFV, has been recommended by the WHO to treat chronic HBV infection (WHO, 2015) since 2015, particularly in pregnant women (Lin et al, 2018;Bierhoff et al, 2020). TDF received US FDA approval for HIV in 2001 first, and approval for HBV in 2008, administered at a dose of 300 mg once daily.…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection in adults results in chronic hepatitis in less than 5% of cases, whereas in infants and young children, it causes the development of a chronic form of the disease in 95% of subjects ( 5 ). Knowing the hepatitis B status of pregnant women is critical for effective disease management and prevention of mother-to-child transmission ( 6 ). Prevalence rates of hepatitis B among pregnant women varied considerably from one study site to another, ranging from 1.1 to 9.6% in Cameroon ( 7-9 ).…”
Section: Discussionmentioning
confidence: 99%